Obesity and the lung: what we know today - Brock, Judith; Billeter, Adrian; Müller, Beat P.; Herth, Felix (Respiration, 2021)
Obesity is becoming more and more prevalent especially in Western industrial nations. The understanding of adipose tissue as an endocrine organ as well as the detection of adipocytokines - hormones that are secreted from the adipose tissue - gave reason to examine the interactions between adipose tissue and target organs. These efforts have been intensified especially in the context of bariatric surgery as promising weight loss therapy. Interactions between the lung and adipose tissue have rarely been investigated and are not well understood. There are obvious mechanical effects of obesity on lung function explaining the associations between obesity and lung diseases, in particular obesity hypoventilation syndrome, obstructive sleep apnea syndrome, asthma, and chronic obstructive pulmonary disease. The rise in the prevalence of obesity affects the epidemiology of pulmonary diseases as well. The aim of this review is to summarize the current knowledge on interactions, associations, and consequences of obesity and weight loss on lung function and lung diseases. Based on these data, areas for future research are identified.
Online veröffentlicht: 26. November 2020
Gesehen am 25.03.2024